DAYA TERIMA DAN NILAI GIZI KERIPIK PANGSIT DENGAN SUBSTITUSI TEPUNG BAYAM DAN TEPUNG IKAN TERI SEBAGAI MAKANAN SELINGAN PENCEGAH ANEMIA PADA REMAJA PUTRI - pakae, maria angela; Nur, Astuti; Sine, Juni Gresilda L (Kupang Journal of Food and Nutrition Research, 2024)
ABSTRACT Nutritional problems that often occur in teenager girls are anemia. Based on data (Riskesdas, 2018), almost half of the Indonesian population suffers from anemia nutritional problems with the number of cases reaching 48.9%. Therefore, it is necessary to modify the recipe from local food ingredients by substituting spinach flour and anchovy flour in wonton chips products to prevent anemia in teenager girls.This study aims to determine the acceptability and nutritional value of wonton chips with spinach flour and anchovy flour substitution. The research design used an experimental method in 4 treatments, namely the first treatment P0 as a control, treatments P1, P2, and P3 respectively, namely spinach flour (5%, 10%, 15%) and anchovy flour (15%, 10%, 5%) with organoleptic tests carried out by 30 semi-trained panelists. Statistical analysis was performed using the Kruskal Wallis test and continued with the Mann-Withney test for significantly different data, while the nutritional value was tested using TKPI 2017. The results of the organoleptic test showed that the substituted wonton chips of spinach flour and anchovy flour had a significant effect on the color, aroma, taste and texture of wonton chips with a p value <0.05. The most preferred wonton chips in terms of color were P1, aroma was P2, texture was P1 and P3, taste was P2. While the results of the nutritional value test showed that the formula with the nutritional content closest to the needs of teenage girls' snacks was P2 with a total energy of 1119.4 kcal, 35.2 grams of protein, 60.3 grams of fat, 111.2 grams of carbohydrates and 5.8 milligrams of Fe. The results of the organoleptic and nutritional value tests showed that the most recommended product was the product from the P2 formula with a ratio of spinach flour and anchovy flour of 10%: 10%. Further research is expected regarding the content or analysis of other micronutrients from the wonton chips formulation.